Quantification of biometric growth and litterfall dynamics of four-year-old Dendrocalamus stocksii at differential spacing regime in humid tropics of central Kerala, India - Maurya, Lalitkumar Lekuprasad; V Jamaludheen; T K Kunhamu (Indian Journal of Agroforestry, 2025)
Dendrocalamus stocksii (solid bamboo), a wild bamboo species native to the central Western Ghats of India, holds significant commercial value. Despite being a prioritized species, its productivity performance is still relatively unexplored compared to other bamboo species. Therefore, a praxis-oriented field study was undertaken in the humid tropics of Kerala to evaluate the biometric growth performance, leaf area index (LAI), and litterfall dynamics of four-year-old D. stocksii at differential spacing regime (8 × 8 m, 8 × 6 m, 8 × 4 m). Results revealed that all these attributes were manifested by planting spacings, highlighting the importance of regulating planting spacing/density for optimizing the growth and productivity of D. stocksii. With increase in spacing from 8 × 4m (closest) to 8 × 8m (widest), most growth parameters (culm diameter, girth, crown width, culms/clump) increased, except for culm height and internodal length. Litterfall followed a seasonal bimodal pattern with a major peak in the dry months (Mid-January to Mid-February) and a minor peak in Mid-May to Mid-June. Highest litterfall was observed in closest spacing (10.10 Mg ha–1), while lowest at widest spacing (7.86 Mg ha–1). LAI also followed similar trend. However, management objectives can play a central role in determining the optimal bamboo spacing for farmers. Moreover, its abundant litterfall has the potential to enhance on-site enrichment and improve soil fertility through leaf litter accumulation, particularly in nutrient-poor, degraded soils. Likewise, D. stocksii- compact clump circumference, thornless, easily manageable- is also advisable as a promising bamboo species, in the context of sustainable and resilient multitier agroforestry systems to diversify economic returns and promote the overall usefulness of the species across humid tropics of central Kerala and the Western Ghats.